La motricidad fina y su incidencia en la coordinación óculo manual en los niños y niñas de primer año de educación básica de la escuela fiscal Galo Plazo Lasso de la ciudad de Machala, periodo lectivo 2013 - 2014. - Solano Macanchí, Verónica del Cisne (2015)
This research deals with fine motor skills such incident factor in the development of hand-eye coordination in children of first year of basic education Galo Plaza Lasso Machala City Public School, aims to detect deficiencies that develop in children associated with eye-hand, little practical product of fine motor coordination.